Síndrome inflamatorio multisistémico en niños con COVID-19: una visión desde la reumatología - Naranjo Arango, Yonatan Andrés (Revista Colombiana de Reumatología, 2021)
The coronavirus disease 2019 (COVID-19) produced by SARS-CoV-2 has taken on great importance in recent months, and is under constant investigation by different areas of medicine, including rheumatology, in search of the best evidence scientific. In the case of the paediatric population, it is particularly important as it was first thought that the impact of the pandemic in this population would be less due to the low presence of severe cases. Evidence is now being reported of clinical pictures in children with a diagnosis of COVID-19 who are characterised by an altered inflammatory state consisting of a storm of pro-inflammatory cytokines that produces manifestations similar to those presented in autoimmune diseases, such as Kawasaki disease. It has been called Multisystemic Inflammatory Syndrome in children, temporarily associated with SARS-CoV-2 which, in many cases requires hospitalisation in paediatric intensive care units and multidisciplinary management by various specialties.